“Sang Kuriang” Drama Script by Utuy T. Sontani for Learning Material in Drama Apreciation Learning Senior High School Class XII - Gina Devina (LOKABASA, 2022)
This research is taken from the drama script "Sang Kuriang" by Utuy T. Sontani which was divided into two parts, namely libretto, two rounds, and three-part drama. The purpose of this study is to describe the two-round drama scripts in the form of (1) the facts of the story in the drama script "Sang Kuriang by Utuy T. Sontani which includes the facts of the story (lines, characters, and settings), (2) moral values (religious, psychological and social aspects), and (3) the application of the fact story and moral values analysis results for learning material of drama appreciation in class XII high school. The method used in this study is the descriptive analysis method with literature review techniques, data analysis, and interpretation. The results of his research are; (1) this drama script has a social-religious theme regarding a child named sangkuriang who loves his mother. The facts of the story found include the forward flow and the characters found are divided into two main characters and additions, the background is the setting of the place and time, (2) this drama has a sign that contains meaning, Lessons can be learned from the story the legend of Tangkuban Perahu is never undermine the trust given, especially with how to kill his faithful that continues to accompany private interests to be sacrificed. Sangkuriang is an example that should not be imitated, his heart, his mother's wrath get a reply. Although the messages are conveyed from the legend of Tangkuban Perahu is make your parents happy in a good way and not contrary to the prevailing norms and values, (3) the fact of the story and moral values of the drama script “Sang Kuriang” by Utuy T. Sontani can be used as learning material because it is by the criteria for selecting teaching materials positive in the story.